A Critical Review of "Theoretical and Practical Bases of Film Music: An Essay on Film Music in the World of Islam" - Hamid Askari Rabori (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book titled "Theoretical and Practical Bases of Film Music: An Essay on Film Music in the World of Islam", is the first published book in Iran which deals with the study of theoretical and practical fundaments of the use of film music. By employing a fresh look, the book investigates the most important elements and instruments in music and drama in the context of "The common Expression Potentially". By reviewing the role of the film music in Egyptian silver screen, it shows new aspects of music in Islamic countries’ cinema, as viewed by the Eastern artists. In addition, by comparing the two religious films i.e. Mohammad the Messenger and The Passion of the Christ, from the view of film music representation, the favorable performance of the film for expressing the semantic layers of the film has been designed. The present paper has pointed out some certain strengths of the book such as the good quality of studying the artistic elements and instruments of music and drama, coherent and multilateral analyses relevant to the Egypt cinema, innovation in raising the point of representation of the music of religious films and expressive and fluent expression. Also, with respect to the form of the book, typography, the printing quality of the photos, editing and misprints can be mentioned.  Through the analysis of the content, it has dealt with issues such as the effect of lacking the title of the second chapter which deals with semantic coherence, the non-comprehensiveness of the topics such as “form and choosing instruments, and “music representation” due to a weak compilation and insufficient references to the available sources